Recent Advances in Tantalum Carbide MXenes: Synthesis, Structure, Properties, and Novel Applications - Mingfeng Li; Li Xu; Mengdi Guo; Hao Shang; Xiao Luo; Yanan Ma (Crystals)
Tantalum carbide MXenes, notably Ta4C3Tx and Ta2CTx, exhibit distinctive physicochemical properties that distinguish them from the well-studied Ti3C2Tx MXene. The combination of exceptional electrochemical properties, efficient photothermal conversion, and tunable surface terminations highlights the versatility of Ta-MXenes. These characteristics render them highly valuable for versatile applications. This minireview summarizes recent progress in tantalum carbide MXenes and their composites, focusing on applications in energy storage, conversion, sensing, and biomedicine. First, synthesis methods for tantalum carbide MXenes are summarized. Subsequently, their key properties are discussed, followed by a systematic review of diverse applications. Finally, this review offers a summary and outlook on the challenges and opportunities in the field of tantalum carbide MXenes research.